Effectiveness of a novel mobile health (Peek) and education intervention on spectacle wear amongst children in India: Results from a randomized superiority trial in India - Morjaria, Priya (EClinicalMedicine, 2020)
BACKGROUND: Uncorrected refractive errors can be corrected by spectacles which improve visual functioning, academic performance and quality of life. However, spectacle wear can be low due to teasing/bullying, parental disapproval and no perceived benefit. Hypothesis: higher proportion of children with uncorrected refractive errors in the schools allocated to the intervention will wear their spectacles 3–4 months after they are dispensed. METHODS: A superiority, cluster-randomised controlled trial was undertaken in 50 government schools in Hyderabad, India using a superiority margin of 20%. Schools were the unit of randomization. Schools were randomized to intervention or a standard school programme. The same clinical procedures were followed in both arms and free spectacles were delivered to schools. Children 11–15 years with a presenting Snellen visual acuity of <6/9.5 in one or both eyes whose binocular acuity improved by ≥2 lines were recruited. In the intervention arm, classroom health education was delivered before vision screening using printed images which mimic the visual blur of uncorrected refractive error (PeekSim). Children requiring spectacles selected one image to give their parents who were also sent automated voice messages in the local language through Peek. The primary outcome was spectacle wear at 3–4 months, assessed by masked field workers at unannounced school visits. www.controlled-trials.com ISRCTN78134921 Registered on 29 June 2016 FINDINGS: 701 children were prescribed spectacles (intervention arm: 376, control arm: 325). 535/701 (80%) were assessed at 3–4 months: intervention arm: 291/352 (82.7%); standard arm: 244/314 (77.7%). Spectacle wear was 156/291 (53.6%) in the intervention arm and 129/244 (52.9%) in the standard arm, a difference of 0.7% (95% confidence interval (CI), -0.08, 0.09). amongst the 291 (78%) parents contacted, only 13.9% had received the child delivered PeekSim image, 70.3% received the voice messages and 97.2% understood them. INTERPRETATION: Spectacle wear was similar in both arms of the trial, one explanation being that health education for parents was not fully received. Health education messages to create behaviour change need to be targeted at the recipient and influencers in an appropriate, acceptable and accessible medium. FUNDING: USAID (Childhood Blindness Programme), Seeing is Believing Innovation Fund and the Vision Impact Institute.